Identification of Risk Mitigation Due to Noise in The G2R Production Area at PT OMI - Najwa Adis Prambanan; Agung Prayudha Hidayat (Batrisya Education, 2025)
Production activities are the core of a manufacturing company. To produce goods, production activities are necessary. Concentration or focus is one of the factors determining the success of the production process. Through interviews with one of the G2R relay production supervisors, it was found that there is an issue related to the decreased concentration of operators working in the G2R relay production area. This indirectly affects the operators' work performance, which in turn impacts the quality of the products produced. The root cause of the decreased concentration was found to be the production machines generating very loud noise. The objective of this final project is to minimize the risks caused by this noise. Therefore, the House of Risk (HOR) method will be used as the solution method. The House of Risk (HOR) can identify risk events, risk agents, and propose mitigation strategies. The HOR calculation for this project suggests a mitigation strategy of applying proper or thicker machine covers to reduce noise from the production machines.